Plant Antimicrobial Peptides as Potential Tool for Topic Treatment of Hidradenitis Suppurativa - Santos-Silva, Carlos André dos; Tricarico, Paola Maura; Vilela, Lívia Maria Batista; Roldan-Filho, Ricardo Salas; Amador, Vinícius Costa; d’Adamo, Adamo Pio; Rêgo, Mireli de Santana; Benko-Iseppon, Ana Maria; Crovella, Sergio (Frontiers in Microbiology, 2021)
Among chronic skin autoinflammatory diseases, Hidradenitis Suppurativa (HS) stands out for its chronicity, highly variable condition, and profound impact on the patients’ quality of life. HS is characterized by suppurative skin lesions in diverse body areas, including deep-seated painful nodules, abscesses, draining sinus, and bridged scars, among others, with typical topography. To date, HS is considered a refractory disease and medical treatments aim to reduce the incidence, the infection, and the pain of the lesions. For this purpose, different classes of drugs, including anti-inflammatory molecules, antibiotics and biological drugs are being used. Antimicrobial peptides (AMPs), also called defense peptides, emerge as a new class of therapeutic compounds, with broad-spectrum antimicrobial action, in addition to reports on their anti-inflammatory, healing, and immunomodulating activity. Such peptides are present in prokaryotes and eukaryotes, as part of the innate eukaryotic immune system. It has been proposed that a deregulation in the expression of AMPs in human epithelial tissues of HS patients may be associated with the etiology of this skin disease. In this scenario, plant AMPs stand out for their richness, diversity of types, and broad antimicrobial effects, with potential application for topical systemic use in patients affected by HS.